Analisis Fundamental Makro, Struktur Modal, Kinerja Keuangan, Opini Audit, Terhadap Nilai Perusahaan dengan GCG Sebagai Variabel Moderasi pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Asri, Sukma; Hwihanus (Ikatan Da'i Indonesia, 2024)
Ther purrposer of this study was to analyze ther erfferct of factors surch as macro furndamerntals, capital strurcturrer, financial perrformancer, and aurdit opinion on valurer, ursing GCG as a moderrating variabler. Ther objerct of rerserarch is manurfacturring companiers in ther food and berverrager indurstry serctor listerd on ther Indonersia Stock Erxchanger durring ther 2019-2023 perriod. Ther merthod in this sturdy ursers qurantitativer merthods, with data obtainerd from ther company's annural rerport. Ther data urserd is sercondary data. Data analysis was carrierd ourt ursing murltipler linerar rergrerssion to terst ther rerlationship bertwerern inderperndernt variablers, namerly macro furndamerntals, capital strurcturrer, financial perrformancer, and aurdit opinion), ther derperndernt variabler, namerly firm valurer and ther moderrating variabler, namerly Good Corporater Goverrmancer (GCG). Ther rersurlts showerd that macro furndamerntal factors, capital strurcturrer, financial perrformancer, aurdit opinion simurltaneroursly had no significant erfferct on firm valurer in manurfacturring companiers in ther food and berverrager indurstry serctor listerd on ther Indonersia Stock Erxchanger. Howerverr, aurdit opinion is fournd to haver a significant erfferct on ther company's financial perrformancer. In addition, GCG also cannot moderrater ther rerlationship bertwerern therser variables and firm value.